2017
DOI: 10.1111/1742-6723.12774
|View full text |Cite
|
Sign up to set email alerts
|

De‐labelling self‐reported penicillin allergy within the emergency department through the use of skin tests and oral drug provocation testing

Abstract: Selected patients in the ED who self-report an allergy to penicillin can be safely tested there for penicillin allergy, using skin tests and oral drug provocation testing. This testing allows a significant de-labelling of penicillin allergy, with the majority of these patients able to tolerate penicillin without incident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
1
35
0
1
Order By: Relevance
“…Recent work by Trubiano et al . identified that 24% of patients in acute care units, including ICU, had an AAL , while more specifically, up to 8–12% of patients in the emergency department and 8% in the ICU have a penicillin AAL . The reason for this high prevalence of AALs is probably multifactorial and includes those accumulated in childhood during a concurrent viral illness (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work by Trubiano et al . identified that 24% of patients in acute care units, including ICU, had an AAL , while more specifically, up to 8–12% of patients in the emergency department and 8% in the ICU have a penicillin AAL . The reason for this high prevalence of AALs is probably multifactorial and includes those accumulated in childhood during a concurrent viral illness (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…After testing in this cohort, guideline‐preferred antibiotic prescribing significantly improved (95% [3 months after implementation] v 62% [3 months before implementation]), as did antibiotic appropriateness (adjusted OR, 12.27; 95% CI, 5.00–30.09) 21 . In another recent Australian study using allergy testing in an emergency department, 81% of patients had their penicillin allergy label removed following penicillin skin testing and oral provocation 22 …”
mentioning
confidence: 82%
“…There have been a number of international initiatives to de‐label patients with amoxicillin allergy including through the American Academy of Allergy, Asthma and Immunology and the North American Choosing Wisely initiatives . There has also been a surge of studies aiming to de‐label beta‐lactam allergy, including perioperative programmes, pharmacy‐led programmes, inpatient programmes and Emergency Department‐led programmes, which have demonstrated resounding success at de‐labelling this allergy and improving antibiotic stewardship in both inpatient and outpatient settings…”
Section: The Necessity Of Ruling Out Amoxicillin Allergy In Childrenmentioning
confidence: 99%